Children's learning of tennis skills is facilitated by external focus instructions - Ricardo Hadler; Suzete Chiviacowsky; Gabriele Wulf; José Francisco Gomes Schild (Universidade Estadual Paulista (UNESP), 2014)
The present study examined the effects of instructions promoting external versus internal foci of attention on the learning of a tennis forehand stroke in 11-year old children. Three groups of participants practiced hitting tennis balls at a target. External focus group participants were instructed to direct their attention to the movement of the racquet, while participants in the internal focus group were asked to direct their attention to the movements of their arm. Participants in a control group did not receive attentional focus instructions. Two days after the practice phase (60 trials), learning was assessed in retention and transfer tests. The results showed that the external focus group demonstrated greater accuracy in hitting a target relative to the two other groups in retention, and relative to the internal focus group in transfer. We conclude that instructions inducing an external focus of attention can enhance children's sport skill learning.